PESTICIDES DEPOSITION IN VINEYARDS ON DIFFERENT CONDITIONS OF LEAF WETNESS - Saab,Otavio J. G. Abi (2017)
ABSTRACT The high susceptibility to diseases of fine table grapes cultivars demand intensive use of pesticides, and the presence of water on the leaf surface can worsen the deposition of these products. The objective of this study was to evaluate the spray deposition in vine leaves in different conditions of leaf wetness, and test the effectiveness of an artificial ventilation method to remove water on the leaf surface. We evaluated the spray deposition in vine applied over: wet canopy (presence of high leaf wetness); canopy dried artificially (dried with air jet from air-assisted sprayer, wind speed of 25 km h−1) and canopy dried naturally (naturally dried leaves and free of water on its surface). Saline marker was used in the spray and the deposition on the canopy was determined by conductimetry. A pesticide application in vine, with the presence of water in the leaf surface, causes losses by run-off and reduces the deposit of spraying. The use of air jet formed by air-assisted sprayer fan is efficient for the removal of water on the vine leaf surface and its use can increase the favorable period for the application of pesticides without causing dilution and losses by run-off of the applied product.